The Rousseff impeachment and the crisis of democracy in Brazil. Issue 3 (3rd July 2017) - Avritzer, Leonardo
ABSTRACT: This is an article about the impeachment in Brazil. I argue that it was the result of the political crisis that takes place in the country since 2013. T his political crisis has at least two major components: (1) the first one is the collapse of the coalition presidential system associated with the ascension of a conservative group within the National Congress led by Eduardo Cunha ; (2) the second is a crisis of representation expressed by the increase of illegal campaign financing and the influence of money in Congress. Together, the opposition and the conservative block of the PMDB blocked every move of Dilma Rousseff's administration and proposed moral and economic conservative legislations. After impeaching the president, this group is proposing legislations that pose under threat the democratic system built in the country after 1988.